Description of new species of Ambrosiodmus Hopkins and Dryocoetoides Hopkins (Curculionidae: Scolytinae: Xyleborini) from Mexico - Silva, Mauricio Pérez; Atkinson, Thomas H.; Martínez, Armando Equihua; de La Cruz, Manuel Pérez (Zootaxa, 2020)
Two new species of ambrosia beetles in the Xyleborini from southeastern Mexico are described and illustrated: Ambrosiodmus spinosus n. sp. and Dryocoeetoides tuberculatus n. sp.